Optimization of Crude Palm (Elaeis guineensis) Oil Bleaching using Zeolite-Fe by Response Surface Methodology - Ulfah Anis; Ria Millati; Chusnul Hidayat (agriTECH, 2022)
A carcinogenic 3-monochloropropane 1, 2 diol ester (3-MCPD ester) can be formed during processing crude palm oil (CPO). Chlorine is one of the precursors for the formation of 3-MCPD esters. This study aimed to optimize the bleaching conditions using zeolite-Fe for reducing chlorine concentration by the Response Surface Methodology (RSM) and further evaluate the characteristics of the bleached CPO. Factors such as bleaching time, zeolite-Fe concentration, and bleaching temperature were evaluated and further optimized. The results showed that Fe in the modified zeolite-Fe increased about 71.89% compared to natural zeolite. Zeolite-Fe concentration, bleaching time, and bleaching temperature had a significant effect on chlorine adsorption. The optimum bleaching process was obtained at a zeolite-Fe concentration of 5% (w/w) and bleaching temperature of 80 °C for 30 minutes. Bleached CPO had a chlorine concentration of 25 ± 1 ppb, carotenoid of 467.70 ± 13.71 ppm, and a DOBI (Deterioration Of Bleachability Index) value of 2.17 ± 0.01 R.